Exhausted T cell signature predicts immunotherapy response in ER-positive breast cancer - Manuela Terranova-Barberio (Nature Portfolio, 2020)
ER-positive breast cancer patients do not usually respond to immunotherapy. In this phase II clinical trial, the authors report the safety and efficacy of combining vorinostat and pembrolizumab with tamoxifen in ER-positive breast cancers and provide evidence that T-cell exhaustion may serve as a potential signature for the response of this combination therapy.